Correlation between temporal muscle thickness and grip strength in hemiplegic patients with acute stroke - Park, Jisoo; Park, Jihye; Kim, Soye; Kim, Dong Chan (Frontiers in Neurology, 2023)
Recently, temporal muscle thickness (TMT) has been investigated as a novel surrogate marker for muscle mass and function in neurologic patients. This study aimed to assess the correlation of TMT with grip strength to establish a new parameter for predicting pre-stroke sarcopenia. A total of 358 patients who were newly diagnosed with acute ischemic stroke at our institution between November 2021 and August 2022 were enrolled. Eighty-four patients met the eligibility criteria. The mean TMT was measured within initial brain MRI using previously described methods. Pearson's correlation analyses assessed the relationship between grip strength and TMT. Multiple logistic regression analyses were performed to identify associations between TMT and other associated factors including grip strength, sarcopenia risk, body mass index, age, Charlson Comorbidity Index and Geriatric nutrition risk index. Mean TMT values indicated a strong correlation with the grip strength of the non-hemiplegic hand in both male and female patients. Multiple logistic regression analyses showed that TMT was associated with grip strength and sarcopenia risk in hemiplegic patients. Measuring TMT using cranial MR images during the initial stages of stroke could help predict a patient's pre-stroke muscle strength status. Further studies are required to apply TMT in pre-stroke sarcopenia diagnosis.